'Love knows no (spatial) boundaries?': Investigating diversity in the residential location choices of rural-residing couples upon union formation. (January 2023) - Ferguson, Sara; Catney, Gemma
Abstract: This paper focuses on the residential location choices made by rural-residing couples with diverse residential biographies at union formation. We explore how this decision-making process is navigated and negotiated as a newly formed household. The study is informed by prior research that has aided our understanding of the relational nature of moving and staying processes, and the integral role of life course transitions in shaping residential decisions. We use data from the wider STAYin(g)Rural project, including a large household survey and in-depth interviews with individuals living in rural Northern Ireland (specifically, the case study site of the Clogher Valley, County Tyrone) who have undergone union formation, and decided to either move to, or stay within, the area. We find that, despite considerable heterogeneity within and between couples in their residential biographies, several common, often inter-related, themes dominated their rural residential location choices. Underpinning much of the desire to live and stay in the rural was a strong sense of belonging and attachment to the area, with a complex interplay of economic, environmental, geographical, and social factors acting to enable staying. Clear generational differences in the decision-making process emphasise the importance of exploring distinctions between and across life course stages in studies that aim to understand the process of (rural) staying . Highlights: There is considerable heterogeneity, within and between, rural-residing couples. Couples make proactive, joint decisions to live in rural areas upon union formation. Multiple economic and non-economic factors influence decisions to stay rural. Gender and generation influence the rural residential location choice of couples.